EVALUATION OF AUTOPHAGY FLUX LC3 GENE EXPRESSION AND SERUM IFN-? IN PULMONARY TUBERCULOSIS PATIENTS (Iraqi Journal of Medical Sciences, 2020)
Background: Mycobacterium tuberculosis (Mtb) is the major causal pathogen of human tuberculosis (TB). Autophagy is a highly conserved cytosolic pathway influencing the immune responses and the elimination of intracellular pathogens including Mtb.Objective: To evaluate the effect of Mtb on autophagy flux with autophagy related genes of LC3I and LC3II, beside the evaluation of serum interferon-gamma (IFN-?) level in patients with pulmonary TB.Methods: A total of 50 blood samples were collected from patients with pulmonary TB, besides 30 as healthy control. The real-time polymerase chain reaction (PCR) method was determined the measuring of mRNA expression of autophagy-related genes of LC3I and LC3II. Serum IFN-? protein concentration was measured using sandwich Enzyme Linked ImmunoSorbant assay.Results: The present study showed an increasing in LC3-I level in newly-diagnosed pulmonary TB patients rather than in the control group despite statistically non-significant P?0.05, while LC3-II showed decreasing in all pulmonary TB groups but statistically non-significant P?0.05. Autophagy flux ratio of LC3-I and LC3-II genes showed a statistically significant decrease in pulmonary TB groups especially in newly- diagnosed (p value=0.02) rather than control groups. Moreover, the study of the serum level of IFN-? showed an increase in the level of IFN-? with p=0.0001 in pulmonary TB patients in comparison with the control group. In addition, the correlation between autophagy-related genes and IFN-? have been shown a positive significant correlation (p value =0.013) in the multidrug-resistant (MDR) TB group.Conclusion: Autophagy flux ratio showed a statistically significant decrease in pulmonary TB groups particularly in newly-diagnosed TB patients rather than control groups, this indicates the different modulation factors that may affect the process of autophagy. The only positive correlation within biomarkers of the present study has been shown that LC3-II is a dependent factor on IFN-? in MDR group.Keywords: Pulmonary tuberculosis, autophagy flux, LC3-I, LC3-II, diagnosis, IFN-?Citation: Wahwah SA, Abdulrahman TR, Mankhi AA. Evaluation of autophagy flux LC3 gene expression and serum IFN-???? in pulmonary tuberculosis patients. Iraqi JMS. 2020; 18(1): 52-60. doi: 10.22578/IJMS.18.1.8
Keywords: Pulmonary tuberculosis; autophagy flux; LC3I; LC3II; diagnosis; IFN